2021
DOI: 10.1113/ep089482
|View full text |Cite
|
Sign up to set email alerts
|

Individual variation of follicular phase changes in endothelial function across two menstrual cycles

Abstract: Evidence regarding the impact of menstrual phase on endothelial function is conflicting, and studies to date have examined responses only over a single cycle.It is unknown whether the observed inter-individual variability of phase changes in endothelial function reflects stable, inter-individual differences in responses to oestrogen (E 2 ; a primary female sex hormone). The purpose of this study was to examine changes in endothelial function from the early follicular (EF; low-E 2 ) phase to the late follicular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…However, the present paper byLiu et al (2021) used this three-step method and still discovered substantial variability within and between menstrual cycles, demonstrating that the conflicting findings reported in the research to date might not be fully explained solely by methodological differences. Additionally, whilst the threestep method is suitable for identifying and verifying menstrual cycle phase, it might not be sufficient for eliminating heterogeneity within menstrual cycle research Liu et al (2021). examined the group-level and intra-individual reproducibility of early follicular to late follicular changes in FMD across two consecutive menstrual cycles in healthy, eumenorrhoeic women.…”
mentioning
confidence: 54%
See 4 more Smart Citations
“…However, the present paper byLiu et al (2021) used this three-step method and still discovered substantial variability within and between menstrual cycles, demonstrating that the conflicting findings reported in the research to date might not be fully explained solely by methodological differences. Additionally, whilst the threestep method is suitable for identifying and verifying menstrual cycle phase, it might not be sufficient for eliminating heterogeneity within menstrual cycle research Liu et al (2021). examined the group-level and intra-individual reproducibility of early follicular to late follicular changes in FMD across two consecutive menstrual cycles in healthy, eumenorrhoeic women.…”
mentioning
confidence: 54%
“…In a recent systematic review and meta-analysis investigating the effects of menstrual cycle phase on exercise performance, we highlighted that few of the included studies used the trio of recommended methods to identify and verify menstrual cycle phases, which might partly explain the large between-study variance reported in the results(McNulty et al, 2020). However, the present paper byLiu et al (2021) used this three-step method and still discovered substantial variability within and between menstrual cycles, demonstrating that the conflicting findings reported in the research to date might not be fully explained solely by methodological differences. Additionally, whilst the threestep method is suitable for identifying and verifying menstrual cycle phase, it might not be sufficient for eliminating heterogeneity within menstrual cycle research Liu et al (2021).…”
mentioning
confidence: 81%
See 3 more Smart Citations